Shoulder joint replacement can improve quality of life and outcome in patients with dysmelia: a case series. Issue 1 (December 2016) - Merkle, Tobias; Beckmann, Nicholas; Bruckner, Tom; Zeifang, Felix
Abstract Background Arthroplasty is a proven treatment option for glenohumeral osteoarthritis. Common indications include primary or posttraumatic osteoarthritis, avascular necrosis of the humeral head, rotator cuff tear arthropathy and rheumatoid osteoarthritis. Arthroplasty is rarely performed among patients with glenohumeral dysmelia. An overuse of the upper limb in patients with thalidomide-induced phocomelia and people with similar congenital deformities like dysmelia results in premature wear of the shoulder joint. This study aims to evaluate our experience with cases of glenohumeral osteoarthritis caused by dysmelia and treated with arthroplasty. To date, few reports on the outcome of shoulder arthroplasty exist on this particular patient group. Case presentation We included four dysmelic patients (five shoulders) with substantial glenoid dysplasia in a prospective database after approval by the local ethics committee. Once conservative treatment options had been exhausted, the patients were treated with shoulder arthroplasty and assessed clinically and radiographically before and after surgery. The mean patient age at the time of surgery was 50.4 years. The minimum follow-up time was 24 months (24–91 months). All patients experienced a considerable improvement of range of motion (ROM) and a relief of pain. No intra- or postoperative complications appeared. Conclusion Patients with dysmelia have acceptable short and mid-term results with resurfacing hemiarthroplasty. It is an effective although somewhat complicated method to relieve pain and improve movement. Long-term performance of arthroplasty in patients with dysmelia remains to be seen, particularly with regard to the remaining problem of the altered and often deficient glenoid.